Effects of Post Ischemia-Reperfusion Treatment with Trimetazidine on Renal Injury in Rats: Insights on Delayed Renal Fibrosis Progression. (2nd July 2018) - Park, Jin Ha; Jun, Ji Hae; Shim, Jae-Kwang; Shin, Eun Jung; Shin, Eunah; Kwak, Young-Lan
Abstract : Even after recovery from acute kidney injury, glomeruli remain vulnerable to further injury by way of interstitial fibrosis. This study is aimed at elucidating the effects of post ischemia-reperfusion (I/R) treatment with trimetazidine on the progression to renal fibrosis as well as short- and intermediate-term aspects. Trimetazidine 3 mg/kg or 0.9% saline was given intraperitoneally once upon reperfusion or daily thereafter for 5 d or 8 w. Renal histologic changes and related signaling proteins were assessed. After 24 h, post I/R treatment with trimetazidine significantly reduced serum blood urea nitrogen and creatinine levels and tubular injury accompanied with upregulation of hypoxia-inducible factor- (HIF-) 1 α, vascular endothelial growth factor (VEGF), and Bcl-2 expression. After 5 d, post I/R treatment with trimetazidine reduced renal tubular cell necrosis and apoptosis with upregulation of HIF-1 α -VEGF and tissue inhibitors of metalloproteinase activities, attenuation of matrix metalloproteinase activities, and alteration of the ratio of Bax to Bcl-2 levels. After 8 w, however, post I/R treatment with trimetazidine did not modify the progression of renal fibrosis. In conclusion, post I/R treatment with trimetazidine allows ischemic kidneys to regain renal function and structure more rapidly compared to nontreated kidneys, but not enough to resolute renal fibrosis in long-term aspect.